Chapter The use of 2H and 18O isotopes in the study of coastal karstic aquifers - Lenac, Danijela (Monitoring of Mediterranean Coastal Areas: Problems and Measurement Techniques, 2022)
Complexity of karst groundwater networks requires implementation of standard hydrogeological monitoring and unconventional methods of investigation. We present the results of isotope composition analysis for three karst springs and rain water collected in their hinterland. During two years, spring water samples were collected on a weekly and rain samples on a monthly basis. The main findings are: winter precipitation of Mediterranean origin dominates springs' recharge, a dual porosity model is a fit for the studied systems, and hinterlands of the springs have different retention capabilities.